Optimization of Kraft and Biokraft Pulping for Kenaf V36 - Halis, Rasmina (2010)
To realise the full potential of kenaf derived products to the wood industry more research needs to be done. This study examines the suitability of kenaf V36 to the pulp and paper industry using various pulping processes for future paper manufacturing considerations. The effectiveness of fungal pre-treatments to improve the production of Kraft pulp and paper properties was investigated. The study comprised characterization of kenaf fibres, assessment of pulping conditions, morphological characterisation of selected fungi, pre-treatments and biokraft pulp and paper evaluations. The characterization of kenaf V36 fractions covered the botanical aspects, anatomical structure, fibre morphology and chemical compositions. Anatomically, it was found that the bast fibre consisted of long fibre bundles (2.6 mm) and the core with short fibres (0.64 mm). Vessel elements including axial and ray parenchyma were observed in the composition of the core structure. Bast was composed of 59.7% cellulose with a lower percentage of lignin (13.2%) compared to the core with 34.5% and 19.4%, respectively. The chemical composition showed that kenaf had higher cellulose and lower lignin contents compared to wood. Kraft pulping of kenaf stem using different cooking conditions showed that a combination with 17% of active alkali, 25% sulphidity, a wood to water ratio of 1:7 and a cooking temperature of 170 C for 2 hours yielded 47.2% pulp and produced the optimum paper properties. Beating operation enhanced almost all paper properties of kenaf pulps except for tearing strength. Fungal pre-treatments were carried out for a period of 1, 2, 3 or 4 weeks. The results obtained from SEM and TEM micrographs revealed that each fungus had a different morphology and a unique growth pattern. In degrading kenaf chips each fungus involves a different selection of chemical compounds. The results showed that Coriolus versicolor was a lignin degrader with 38% reduction; Pycnoporus sanguineus fed on holocellulose (22.03%) and cellulose (33.50%) as sources of food whilst Phanerochaete chrysosporium was a milder decomposer on lignin and cellulose throughout the duration of treatments. Treatments with a mix of two fungi indicated a drastic loss of all chemical contents especially on cellulose and lignin contents. Pre-treatments for biokraft pulping required a two-week incubation period. Biokraft pulping treated with single fungus, with different inoculum sizes and nutrient adjuvants were done to investigate the optimal properties of the pulp and paper produced. Pre-treatments yielded a higher percentage of pulp and lower reject values than untreated pulp. The inoculum of 6 x 106 mL/spores and 6:300 v/v nutrients adjuvant is the best condition that improved all pulp and paper properties. Bio-kraft pulping treated with PS produced the highest yield of pulp at 52.6%. Treated pulps tend to have greater conformability and compressibility which resulted in better fibre-to-fibre bonding of paper. Thus, higher quality hand-sheets were produced relative to their untreated counterparts. Among the hand-sheets produced, the C. versicolor treated yielded superior paper properties compared to P. chrysosporium and P. sanguineus except on folding endurance. Biokraft pulping using a mix of two fungi pre-treatments showed better brightness with lower kappa number as compared to single fungal treatments. The treated handsheets showed severe losses in pulp yields and lesser paper strength properties. The reduction in strength was as much as 94% - 96% when compared to the untreated pulps.